The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/3561857
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Surgical Approach for the Management of Acquired Severe Lower Punctal Stenosis

Abstract: Purpose Evaluation of using pigtail probe to detect and open severely stenosed lower lacrimal punctum followed by self-retaining bicanalicular intubation. Study design A prospective nonrandomized clinical study. Methods The study included 24 patients with severe lower punctal stenosis (grade 0 according to Kashkouli scale) attending at Menoufia University Hospitals. The upper punctum and canaliculus were patent. All patients were complaining of epiphora and had a thorough ophthalmological examination including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…One year following surgery, epiphora was nonexistent (grade 0) in 16 eyes (66.7%) and scarcely evident (grade 1) in 4 eyes (16.7 percent). A statistically significant difference compared to the preoperative epiphora was detected12 .At six weeks, 82 percent of the 77 eyes in patients who underwent punctal dilation with Mini Monoka tube insertion rather than snip operations displayed improvement in epiphora, according to Hussain et al But during the 6-week followup, they observed stent migration in one patient and early stent loss in three patients13 . Following up on 87 eyes, Ali et al discovered that while 82 percent of cases showed complete postoperative symptom relief, 10.3 percent of the eyes experienced epiphora and 5.3 percent had restenosis following punctoplasty14 .…”
mentioning
confidence: 87%
“…One year following surgery, epiphora was nonexistent (grade 0) in 16 eyes (66.7%) and scarcely evident (grade 1) in 4 eyes (16.7 percent). A statistically significant difference compared to the preoperative epiphora was detected12 .At six weeks, 82 percent of the 77 eyes in patients who underwent punctal dilation with Mini Monoka tube insertion rather than snip operations displayed improvement in epiphora, according to Hussain et al But during the 6-week followup, they observed stent migration in one patient and early stent loss in three patients13 . Following up on 87 eyes, Ali et al discovered that while 82 percent of cases showed complete postoperative symptom relief, 10.3 percent of the eyes experienced epiphora and 5.3 percent had restenosis following punctoplasty14 .…”
mentioning
confidence: 87%
“…In cases of complete punctal agenesis, interventional treatment with pigtail probe-assisted intubation of both canaliculi using a silicone stent can be considered. This method allows for the localization of the punctal orifice and relatively safe treatment, effectively combating pathological tearing in 66.7% of cases one year after the procedure [12]. Ordinary microsurgical punctoplasty is associated with a high recurrence rate [2].…”
Section: Figure 17mentioning
confidence: 99%
“…Although several factors can cause eyelid malposition [2] , senile involution can significantly weaken horizontal palpebral traction and eventually decrease lower eyelid tension (LET) [3] . Progressive lower eyelid laxity may cause inappropriate ocular exposure and may have unpleasant effects on the aesthetics of the face [4][5][6] . Eventually, this laxity will need to be corrected surgically [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%